Differential Diagnosis of Dystonia - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2003)
An approach to the early diagnosis of pediatric neurotransmitter diseases (PNTD), and especially dystonia, is outlined in a report from the University Children's Hospital, Dusseldorf, Germany; and Institute of Child Health, University College, London, UK.